Prenatal Exposure to Nicotine in Pregnant Rat Increased Inflammatory Marker in Newborn Rat - Yosouf Mohsenzadeh; Asghar Rahmani; Javad Cheraghi; Maryam Pyrani; Khairollah Asadollahi (Mediators of Inflammation)
This study aimed to investigate any inflammatory effect of nicotine on rat embryo by exposing their mothers to different dosages of nicotine during pregnancy. During this experimental study, 32 pregnant healthy Wistar rats were divided into 4 equal groups, including a control and 3 nicotine exposure groups. Injections were performed subcutaneously starting at the first day of pregnancy until parturition. As the dosages of nicotine were increased, the weight gain by pregnant rats and the mean weight of their newborns were significantly reduced. Mean ± SD of hs-CRP was significantly higher among groups exposed to various dosages of nicotine (2, 4, and 6 mg/kg) compared to the control group (P<0.0001) and its increasing rate was also dose dependent. Mean ± SD serum level of IL-6 and TNF-α among all groups exposed to nicotine, except for 2 mg/kg nicotine injected group, was increased significantly (P<0.0001). Mean ± SD of serum level of TGF-β and nitrite oxide among exposure groups showed significant differences compared to the control group only at the dosage of 6 mg/kg (P<0.0001). The current study showed that exposing pregnant rats to nicotine causes a dose dependent increase in the rate of all the studied inflammatory serum markers among their newborns.